Cisco firewalls - Moraes, Alexandre Matos da Silva Pires de. (Indianapolis, IN : Cisco Press, 2011)
Cisco Firewalls thoroughly explains each of the leading Cisco firewall products, features, and solutions, and shows how they can add value to any network security ;design or operation. The author tightly links theory with practice, demonstrating how to integrate Cisco firewalls into highly secure, self-defending networks. Cisco Firewalls shows you how to deploy Cisco firewalls as an essential component of every network infrastructure.
Includes index.
rua 11/10/13
Loans
Keywords: Firewalls (Computer security)